Analysis of stroke rate (SR) and Stroke Length (SL) the Three Fastest Breaststroke Swimmers at the Tokyo Olympics 2021 - Alim, Novan Purnama; Supriatna, Supriatna; Hanief, Yulingga Nanda (CV Rezki Media, 2024)
Background: Swimming velocity results from a combination of stroke rate (SR) and stroke length (SL). Previously, it was rare to find studies that discussed the pattern of SR and SL length in Olympic swimmers, especially in breaststroke swimmers, as a benchmark reference in a study. Objectives: This study aimed to determine the practical pattern of the stroke rate (SR) and stroke length (SL) of 100 m and 200 m breaststroke swimmers ranked first to third at the 2021 Tokyo Olympics. Methods: This study uses quantitative descriptive analysis research with non-test techniques using observation. These non-test techniques involve the systematic observation and recording of the SR and SL length of breaststroke swimmers at the 2021 Tokyo Olympics, as this study aims to determine their patterns. Results: The results of this study show: in the 100 meters breaststroke men's effective SR pattern (45-75 strokes/min) and SL length (1.33-2.14 m/stroke); 200 meters breaststroke men's effective SR pattern (33-49 strokes/min) and SL length (1.55-2.77 m/stroke); 100 meters breaststroke women's effective SR pattern (30-63 strokes/min) and SL length (1-2.14 m/stroke); and 200 meters breaststroke women's effective SR pattern (32-48 strokes/min) and SL length (1.6-2.5 m/stroke). Conclusion: This research concludes that the effective pattern of SR and SL of 100 m and 200 m breaststroke swimmers, as identified in the results, can serve as a benchmark for understanding and improving the performance of competitive breaststroke swimmers.